Wishing to feel better... perceptions of health and illness in persons with rheumatic diseases - Sá, C.; Oliveira, A. (Mediterranean Journal of Social Sciences, 2013)
About a third of the Portuguese population suffers from some form of rheumatic disease. Although the pathology in several persons is mild, these illnesses are chronic and incurable, have a progressive evolution, and the symptoms tend to become increasingly severe. Rheumatic illnesses frequently lead to major consequences for the person’s life disturbing their social relationships, work and leisure. The present work is part of a larger project, and aim to understand how health and illness are represented among adults with rheumatic disease. The data was collected by free associations of words and processed through factorial correspondence analysis. Participants were questioned on what they think and feel about their health and illness. Their perceptions were analysed considering their age, sex and years of illness. The participants point out the illness as their major source of suffering and sadness, revealing they frequently feel discouraged, thinking they are different from other people. Women, more than men, express negative emotions and serious difficulties to maintain a healthy and independent lifestyle - they emphasize their functional limitations that seriously affect daily activities, in particular their mobility and housekeeping tasks. In general, men almost accept their health condition - it is as if they feel strong enough to face their illness and to find ways to improve their wellbeing. What the patients think and feel about their health and illness may convey important information for health professionals, working with patients with rheumatoid disease, in order to help them to improve strategies to deal with this population.